Qur’anic Marriage Values and Marriage Anxiety among Muslim Generation Z - Salman Al Farisi; Stiawan, Thoat; Budiman, Mamdukh; Fakhruddin; Gandhung Fajar Panjalu (Jurnal Ilmiah Al-Mu'ashirah: Media Kajian Al-Qur'an dan Al-Hadits Multi Perspektif, 2026)
The phenomenon of gamophobia, or excessive fear of marriage, is increasingly observed among Muslim Generation Z due to family trauma, economic uncertainty, and exposure to negative narratives about marriage on social media. This situation creates tension between Islamic teachings that present marriage as a source of sakinah, mawaddah, and rahmah and the perceptions of young Muslims who often associate marriage with risk and emotional burden. This study aims to explore how Muslim Generation Z perceive marriage, identify factors contributing to marriage anxiety, and examine how Qur’anic marriage values are understood and interpreted in relation to these concerns. Employing a qualitative approach within the Living Qur’an framework of Ahmad Rafiq, data were collected through in-depth interviews with ten participants in Surabaya, including students, young professionals, a family counselor, and a religious counselor. The data were analyzed using thematic analysis. The findings indicate that marriage anxiety is shaped by family conflict experiences, economic pressures, social media influence, and limited internalization of Qur’anic marriage values. Although most participants were familiar with concepts such as sakinah, mawaddah, rahmah, mutual support, and responsible partnership, these values were often understood at a cognitive level and had not always been translated into emotional confidence regarding marriage. The study identifies a gap between normative religious understanding and personal readiness for marital commitment. The findings suggest that strengthening reflective and contextual engagement with Qur’anic marriage values may contribute to helping Muslim youth develop more constructive perspectives on marriage. This study contributes to Living Qur’an scholarship by examining how Qur’anic teachings on marriage are interpreted within the context of contemporary marriage anxiety among Muslim Generation Z.